Development of Australian clinical practice outcome standards for graduates of critical care nurse education - Gill, F.; Leslie, Gavin; Grech, C.; Boldy, Duncan; Latour, Jos (Blackwell Publishing Ltd, 2015)
Aims and objectives: To develop critical care nurse education practice standards. Background: Critical care specialist education for registered nurses in Australia is provided at graduate level. Considerable variation exists across courses with no framework to guide practice outcomes or evidence supporting the level of qualification. Design: An eDelphi technique involved the iterative process of a national expert panel responding to three survey rounds. Methods: For the first round, 84 statements, organised within six domains, were developed from earlier phases of the study that included a literature review, analysis of critical care courses and input from health consumers. The panel, which represented the perspectives of four stakeholder groups, responded to two rating scales: level of importance and level of practice. Results: Of 105 experts who agreed to participate, 92 (88%) completed survey round I; 85 (92%) round II; and 73 (86%) round III. Of the 98 statements, 75 were rated as having a high level of importance - median 7 (IQR 6-7); 14 were rated as having a moderate level of importance - median 6 (IQR 5-7); and nine were rated as having a low level of importance - median 4 (IQR 4-6)-6 (IQR 4-6). The majority of the panel rated graduate level of practice as 'demonstrates independently' or 'teaches or supervises others' for 80 statements. For 18 statements, there was no category selected by 50% or more of the panel. The process resulted in the development of 98 practice standards, categorised into three levels, indicating a practice outcome level by the practitioner who can independently provide nursing care for a variety of critically ill patients in most contexts, using a patient- and family-focused approach. Conclusion/relevance to clinical practice: The graduate practice outcomes provide a critical care qualification definition for nursing workforce standards and can be used by course providers to achieve consistent practice outcomes.